Impact of Sleep Quality on The Immune System in Adult Individuals - Erika Erika; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
This study aims to explore the relationship between sleep quality and the immune system in adults. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while immune function was evaluated through levels of inflammatory cytokines (such as IL-6 and CRP) and the frequency of infections in the past three months. The results showed that the majority of respondents had poor to moderate sleep quality, which was associated with increased levels of proinflammatory cytokines and a higher frequency of infections. A decline in sleep quality was significantly correlated with a decrease in immune resistance, indicating that poor sleep can disrupt the body's defense mechanisms. Psychosocial factors such as stress were also found to worsen both sleep quality and immune function. These findings highlight the importance of sleep quality in maintaining a healthy immune system, with implications for the development of lifestyle-based interventions to improve sleep quality and immune resilience. This study opens opportunities for further in-depth research on the causal mechanisms between sleep and immunity.